The significance of microbiopsies in cytological smears - Rana K Sherwani; Kafil Akhtar; Prasenjit Sen Ray; Mahfooz Basha (Wolters Kluwer Medknow Publications, 2013)
Background: The role of fine needle aspiration cytology (FNAC) in the diagnosis of malignant lesions is well documented. Conventionally obtained fine needle aspiration (FNA) smears frequently contain well preserved viable intact tissue fragments (microbiopsies). Aims: The present study was aimed at evaluating the microbiopsies and carrying out further cyto-histopathologic correlation in order to assess what additional information they could provide. Materials and Methods: A total of 116 FNA smears from clinically suspected malignant lesions were examined, of which 81 smears (70.0%) contained representative tissue fragments of the tumors. Histopathological details were available in 75 cases. Immunocytochemistry (ICC) was applied in selected smears as and when required. Results: Tumors in which microbiopsies aided in diagnosis chiefly included soft tissue malignancies (12 cases), typed into malignant peripheral nerve sheath tumor, fibrosarcoma, spindle cell sarcoma and malignant melanoma; lung tumors (14 cases) classified as small cell carcinoma, large cell carcinoma, squamous carcinoma and adenocarcinoma; breast tumors (08 cases), typed into ductal, medullary and lobular carcinoma; and lymph node metastasis (19 cases) from primaries in lung, larynx and thyroid. The cyto-histopathologic concordance was raised from 81.2% in the absence of microbiopsies to 93.2% in their presence. Conclusions: FNA smears containing microbiopsies are of ample help in establishing firm diagnosis, tumor typing, and predicting possible primary sites in metastatic tumors which were not possible by cytology alone. Hence, this technique can be utilized to enhance the diagnostic accuracy of FNAC, if put into practice in evaluation of routine cytology smears, without increasing any financial burden on patients.